Soil-Structure Interaction of Flexible Temporary Trench Box: Parametric Studies Using 3D FE Modelling. (21st September 2021) - Alam, Miah; Chaallal, Omar; Galy, Bertrand
Abstract : This paper presents the results of two parametric finite-element studies that were carried out using the PLAXIS-3D finite element (FE) computer code. The following objectives and corresponding parameters were considered: (i) to evaluate the soil pressure on the steel trench box shield; the parameters studied were related to soil type and material, and the study considered till, dry sand, wet sand, and sensitive clay soil; (ii) to assess the effect of trench box material and geometry on earth pressure; the parameters studied were related to trench box material (steel versus aluminum) as well as geometry (plate thickness and strut diameter). These studies included simulation of two steel (or aluminum) trench box shields stacked upon each other to cover the total 6 m (20 ft) deep trench. A Mohr-Coulomb (MC) constitutive material model was chosen for FE analysis (FEA). The FEA results were compared to empirical apparent earth pressure diagrams for a sensitive clay. Comparisons showed that the parameters related to the soil and the trench box have a significant influence on earth pressures.